Comparing configurations for car speed measurements using passive RFID tags - Abou-Rjeily, Chadi (2017)
The ability to detect instantaneous speed is crucial for several applications. Moving objects such as vehicles and robots need to detect their speeds on a regular basis. Current systems measure speed using radars and speedometers which base the detection of the speed on the Doppler frequency shift phenomenon. Furthermore, Global Positioning Systems (GPS) do not usually work inside closed structures. In this paper, we present a cheap alternative to measure speed using RFID passive tags. The system is based on a RFID reader that reads tags installed within its reading range. The reader can be fixed or moving. Several configurations are tested to determine the best spacing of the tags as well as the possible benefit of using an extra antenna to detect speed. Moreover, calculations will be based on three different selection criteria of the time instances.